A CASE STUDY ON CLINICAL PHARMACIST INTERVENTIONS IN THE MANAGEMENT OF DIABETES COMPLICATED CORONARY ARTERY DISEASE IN HEALTH-CARE PRACTICE - KUMAR A, BHARATH; MS, UMASHANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the clinical pharmacist interventions in the management of diabetes complicated coronary artery disease. Methods: In the present study, a case history of a 55-year-old female was suffering from diabetes with coronary artery disease was taken. The case was collected from the cardiology outpatient department in a tertiary care hospital. The case was analyzed from 1 to 3 months. The initial visit to the end of final visit her laboratory parameters was examined at the laboratory. Results: The test report of electrocardiogram revealed sinus rhythm. The patient was advised for an echocardiogram which confirmed coronary artery disease. The patient was subjected to a coronary angiogram, which revealed the presence of double-vessel disease. Her ankle-brachial index study test revealed peripheral artery disease. The patient was diagnosed with coronary artery disease, and she was prescribed with regular medications. The patient was monitored for 1-week duration and prescribed with coronary artery disease medications to normalize the condition. The patient was improved with the treatment and advised for regular follow-ups. Conclusion: The study concludes that there was an imperative need for regular health screening by the physician associated clinical pharmacist care services with an effective treatment modality that can reduce the coronary artery disease incidences in this patient.